Impact of Islamic Branding And Life Style On The Attitude of Wardah Skincare Brand Ambassadors In Bengkulu City According To The Theory Of Reasoned Action (TRA) - Agriani, Salwa Eka; Wahyuni, Eka Sri; Zaki, Khozin (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the influence of Islamic Branding (IB) and Lifestyle (LS) on the attitudes of Wardah skincare brand ambassadors in Bengkulu City. Methodology: A quantitative approach was employed, using primary data collected from 32 respondents through Google Form questionnaires. The data were analyzed using Partial Least Squares (PLS) with SmartPLS version 4.1.0.9. Results: Both Islamic Branding and Lifestyle were found to have a significant positive effect on brand ambassador attitudes toward Wardah skincare. Findings: The study shows that Islamic values embedded in branding, combined with lifestyle alignment, play a crucial role in shaping positive ambassadorial attitudes in a culturally religious setting. Novelty: This research uniquely focuses on brand ambassadors rather than general consumers, within the context of an Islamic-oriented brand in a regional Indonesian city. Originality: It offers fresh insights into how Islamic Branding and Lifestyle jointly influence promotional attitudes, contributing to the literature on religious-based marketing strategies. Conclusion:Islamic Branding and Lifestyle significantly shape positive attitudes of Wardah brand ambassadors. These findings suggest that brands targeting Muslim markets should integrate religious and lifestyle values in their ambassador engagement strategies. Type of Paper: Quantitative Empirical research paper.